2020
DOI: 10.1021/acsami.0c09484
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Mesoporous Silica Nanoparticles with Extra-Large Mesopores for Enhanced Cancer Vaccine

Abstract: Owing to the limitations of conventional cancer therapies, cancer immunotherapy has emerged for the prevention of cancer recurrence. To provoke adaptive immune responses that are antigen-specific, it is important to develop an efficient antigen delivery system that can enhance the activation and maturation of the dendritic cells (DCs) in the human body. In this study, we synthesize hollow mesoporous silica nanoparticles with extra-large mesopores (H-XL-MSNs) based on a single-step synthesis from core–shell mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…Given that MSNs can efficiently load high amounts of cargo, it is feasible to use MSNs for the delivery of cancer vaccines comprising protein antigens and immune adjuvants [ 414 , 415 ]. For example, Lee et al developed an antigen delivery system for enhancing the activation and maturation of dendritic cells using HMSNs with extra-large mesopores (H-XL-MSNs) and a core composed of iron oxide nanoparticles [ 85 ]. The surface of HMSNs was coated with poly(ethyleneimine) to change the surface charge of MSNs, allowing the efficient loading and release of antigens.…”
Section: Update On Msn Applications In Nanomedicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that MSNs can efficiently load high amounts of cargo, it is feasible to use MSNs for the delivery of cancer vaccines comprising protein antigens and immune adjuvants [ 414 , 415 ]. For example, Lee et al developed an antigen delivery system for enhancing the activation and maturation of dendritic cells using HMSNs with extra-large mesopores (H-XL-MSNs) and a core composed of iron oxide nanoparticles [ 85 ]. The surface of HMSNs was coated with poly(ethyleneimine) to change the surface charge of MSNs, allowing the efficient loading and release of antigens.…”
Section: Update On Msn Applications In Nanomedicinesmentioning
confidence: 99%
“…Furthermore, the in vivo studies in tumor-bearing mice showed a significant improvement in tumor suppression and recipient survival. These results suggest that HMSNs with extra-large pores are excellent carriers for cancer vaccines [ 85 ]. Besides, cyclic diguanylate monophosphate can activate the stimulator of interferon genes (STING) pathway, leading to the enhanced tumor immunogenicity, which in turn reverses the immunosuppressive tumor microenvironment.…”
Section: Update On Msn Applications In Nanomedicinesmentioning
confidence: 99%
“…Owing to their mesopores, high surface area, large pore volume, easy modification of physical and chemical functionalities, biocompatibility, and self-adjuvanticity, mesoporous silica nanoparticles (MSNs) are considered to be one of the most promising inorganic nanocarriers [157]. Thalhauser et al proved that covalent conjugates of MSNs and antigens were able to elicit stronger immune responses compared to their noncovalent counterparts in a study where they conjugated HIV-1 envelope trimers onto the surface of MSNs via maleimide-thiol chemistry [158].…”
Section: Protein-inorganic Substance Nanoconjugatesmentioning
confidence: 99%
“…In contrast to this, the MSN has a pore size of around 2 to 20 nm and is widely used for drug delivery [55][56] . Hollow mesoporous (HMSN) SiNPs are spherical-shaped and have a large hole in the center, and they can be used for loading of antigen to activate the immune system 57 . Core-shell SiNP is the spherical silica particle having solid cores and mesoporous shell 58 .…”
Section: Important Characteristic Of Sinpsmentioning
confidence: 99%